SPELT WHEAT GRAIN YIELD AND NUTRITIONAL VALUE RESPONSE TO SOWING RATE AND NITROGEN FERTILIZATION - Sylwia Andruszczak (Journal of Animal and Plant Sciences, 2018)
Due to its valuable chemical composition, spelt enjoys huge interest among consumers and farmers. Research conducted in recent years has focused on winter varieties of this cereal, but there is a lack of information concerning the spring forms of spelt. In a three-year experiment yield and quality grain parameters of new spring breeding lines of spelt (A10 -2 -1 and A12) were evaluated depending on sowing rate (360, 480 and 600 grains m ) and nitrogen rate ( 50 and 80 kg ha ). Higher yield produced the spelt line A12, compared to A10. However, its grain contained less protein, gluten and fat as well as it showed lower contents of N, K, Mg, Zn and Mn. The different sowing rates did not have a significant effect on spelt yield and most of the grain quality parameters evaluated. Higher nitrogen application promoted lodging and caused a reduction in the number of ears per unit area. As a result, the grain yields were significantly lower compared to the rate -1 of 50 kg N ha . Under conditions of the higher nitrogen rate, a higher grain protein and gluten content as well as higher -1 sedimentation index were found, while in turn spelt fertilized at the rate of 50 kg N ha contained more starch and fat. breeding lines is necessary from the point of view of
Keywords: breeding lines of spring spelt; grain chemical composition; nitrogen rate; sowing rate; yield components